DNA barcode reveals the illegal trade of rays commercialized in fishmongers in Brazil - Camacho-Oliveira, Raul B. [UNESP]; Daneluz, Cahique M. [UNESP]; do Prado, Fernanda D. [UNESP]; Utsunomia, Ricardo [UNESP]; Rodrigues, Carlos E.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Elsevier, 2020)
Sequences of the mitochondrial gene COI (DNA Barcode) were used to identify species of rays and skates commercialized in fishmongers in Brazil. The comparisons of the obtained sequences with previously published data available in NCBI and BOLD showed that the fish products corresponded to four species, Hypanus dipterurus, Potamotrygon motoro, Paratrygon ajereba and Gymnura altavela, the last of which is classified as vulnerable according to the IUCN Red List and therefore should not be marketed in accordance with the MMA ordinance 445/2015.
Keywords: COI; Commerce; Fisheries; Gymnura altavela; Species identification; Threatened species